Consequences of Extended Spectrum Beta‐Lactamase–Producing Enterobacteriaceae and Methicillin‐Resistant Staphylococcus aureus Carriage in Awaiting Liver Transplant Patients. Issue 1 (26th October 2020) - Magro, Bianca; Mazzola, Alessandra; Munteanu, Mona; Goumard, Claire; Martinez, Valerie; Bernard, Denis; Scatton, Olivier; Battaglia, Salvatore; Celsa, Ciro; Cammà, Calogero; Conti, Filomena
Abstract : Infections in patients with cirrhosis are associated with liver‐related complications (LRCs), especially in patients awaiting liver transplantation (LT). The aim of this study was to evaluate the impact of methicillin‐resistant Staphylococcus aureus (MRSA) and extended spectrum beta‐lactamase colonization on infections and LRCs for patients on the wait list and on infections after LT. We retrospectively included 250 of 483 patients with cirrhosis who were placed on the wait list for LT from December 2015 to January 2018. These patients were screened for MRSA or extended spectrum beta‐lactamase–producing Enterobacteriaceae (ESBLE) at the time of wait‐list placement and after LT. Of the patients, 76% were male with a mean age of 57.5 ± 10 years, and the most frequent cause of liver disease was alcohol (39%). Median Model for End‐Stage Liver Disease (MELD) score was 19 (12‐28). Only 1 patient was positive for MRSA; 19% of patients (n = 47) had ESBLE fecal carriage at the time of wait‐list placement and 15% (n = 37) had it after LT. Infection‐free survival on the wait list and after LT, according to fecal carriage status, was not statistically different between 2 groups. LRC‐free survival at 6 and 12 months was significantly lower in ESBLE fecal carriage (HR, 1.6; P = 0.04). MELD score >19 (HR, 3.0; P = 0.01) and occurrence of infection during the first 3 months on the wait list (HR, 4.13; P < 0.001) were independent risk factors for LRC occurrence in the multivariate analysis. Our study is the first showing that in a cohort of patients with cirrhosis waiting for LT LRC‐free survival was lower in patients with ESBLE fecal carriage but that infection‐free survival was not different between the 2 groups.